Formation of nanocrystalline and amorphous carbon by high fluence swift heavy ion irradiation of a plasma polymerized polyterpenol thin film precursor. Issue 29 (6th April 2018) - Grant, Daniel S.; Siegele, Rainer; Bazaka, Kateryna; Jacob, Mohan V.
ABSTRACT: This study aimed to produce graphitic‐polymer nanocomposite thin films via the swift heavy ion irradiation of polyterpenol thin films synthesized from an environmentally sustainable precursor by radio‐frequency plasma enhanced chemical vapor deposition. Atomic force microscopy and scanning electron microscopy revealed fluence‐dependent surface restructuring of the thin films leading to the formation of interconnected island structures, with no discernible delamination from the underlying aluminum substrate. Raman spectroscopy confirmed the development of D and G peaks associated with graphitic materials, whilst Fourier transform infrared spectroscopy indicated retention of the plasma polymer's chemical functionalities (including hydroxyl groups) within the material after irradiation. Graphitic‐polymer nanocomposite films prepared by this dry and solvent‐free process have numerous potential applications in biological assay, organic electronics, and membrane technology. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46498. Abstract :